KAPASITAS INDIVIDU, SELF ESTEEM, KOMITMEN ORGANISASI, DAN PENEKANAN ANGGARAN MEMODERASI PARTISIPASI PENGANGGARAN PADA SENJANGAN ANGGARAN - Yuni Sari, Ni Luh Eka; Asmara Putra, I Nyoman Wijana (E-Jurnal Akuntansi, 2017)
This study aims to demonstrate the influence of participation budgeting on budgetary slack with individual capacity, self-esteem, organizational commitment, and budget emphasis as moderating variables. The population was all SKPD in Gianyar, which amounts to 47. The samples in this study were selected based on purposive sampling method, the officials who participated in budget preparation with a minimum term of two years. Data was collected by questionnaire survey method, and a decent questionnaire is processed as many as 141 questionnaires. The data analysis technique used is Moderated Regression Analysis (MRA). The results showed that participation budgeting has a positive influence on budgetary slack, individual capacity is not able to moderate the influence of participation budgeting on budgetary slack, self-esteem and organizational commitment is able to weaken the influence of participation budgeting on budgetary slack, and budget emphasis to strengthen the influence of participation budgeting on budgetary slack in Gianyar SKPD.
Keywords: participation budgeting, budgetary slack, self esteem, organizational commitment, budget emphasis